2013
DOI: 10.1155/2013/720817
|View full text |Cite
|
Sign up to set email alerts
|

A Sub-A Ultrasonic Wake-Up Trigger with Addressing Capability for Wireless Sensor Nodes

Abstract: Wireless sensor nodes spend most of the time waiting either for sensed data or for packets to be routed to the sink. While on board, sensors can raise hardware interrupts to trigger the wake-up of the processor, incoming packets require the radio module to be turned on in order to be properly received and processed; thus, reducing the effectiveness of dynamic power management and exposing the node to unintended packets cause energy waste. The capability of triggering the wake-up of a node over the air would ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Furthermore, due to the rapid developments in low power sensors, microcontrollers, conditioning circuits [6], power management circuits [7], and transmission module and because of efficient wireless sensor networks [8], the power requirement of WSNs is on a sharp decline. The energy harvesting technique [9][10][11][12][13] that is developed two decades ago has the tendency and capability to power these low power WSNs [14]. The energies, those are present in bridge's environment and can be taken into the account for energy harvesting, are vibration (vehicle-induced vibrations), acoustic (vehicle noise), wind (naturally blowing wind and air surges produced due to vehicle motion), and solar.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the rapid developments in low power sensors, microcontrollers, conditioning circuits [6], power management circuits [7], and transmission module and because of efficient wireless sensor networks [8], the power requirement of WSNs is on a sharp decline. The energy harvesting technique [9][10][11][12][13] that is developed two decades ago has the tendency and capability to power these low power WSNs [14]. The energies, those are present in bridge's environment and can be taken into the account for energy harvesting, are vibration (vehicle-induced vibrations), acoustic (vehicle noise), wind (naturally blowing wind and air surges produced due to vehicle motion), and solar.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to the predictions, [Lattanzi et al 2013;Bogliolo et al 2014] adopted a solution at hardware level (called wake-up receiver) to reduce the energy consumption during idle periods, improving the communication between sensor nodes. Simulation results showed that the combination of both mechanisms could lead to larger gains than adopting each technique in isolation.…”
Section: Model Generation In Sensor Nodesmentioning
confidence: 99%
“…It uses offthe-shelf ultrasonic transducers with which a wake-up distance up to 8.6 meter is achieved. Another paper presenting an ultrasonic wake-up receiver with less than 1 μW of energy operating at 40 kHz for wireless sensor networks can be found in [9].…”
Section: Motivationmentioning
confidence: 99%